The Separatist Conflict - Zaripova, Aigul; Zakirov, Aidar (International Journal of Criminology and Sociology, 2022)
There is a strong opinion among researchers of regional processes about the relationship of separatism with ethnicity. For the effective regulation of separatist conflicts, it is important to assess the importance of ethnicity in the development of separatism and to determine whether ethnicity and separatism are always united by a causal relationship. The primary purpose of the study is to focus on the process of ethnicization of separatist conflicts. The focus is on the issue of endowing separatist conflicts with ethnic characteristics; and the causes of the conflicts initially lay in a non-ethnic plane. This study seeks to analyse the reasons for the appeal of separatism to the topic of ethnicity; the instrumental possibilities of ethnicity in the context of separatism are assessed. To that end, the concept of ethnicity in this survey is taken into consideration through the prism of instrumentalism.